To make polymer: quantum dot hybrid solar cells NIR-active by increasing diameter of PbS nanoparticles - Guchhait, Asim; Rath, Arup Kumar; Pal, Amlan J. (Solar Energy Materials and Solar Cells, 2011)
We fabricate NIR-active solar cells based on PbS quantum dots and a conventional conjugated polymer. These devices act as solar cells under exclusively NIR wavelengths above 650 nm. Here PbS nanoparticles absorb photons in the NIR range that in turn generate excitons. We show that with an assistance from a strong electron-acceptor (TiO2), these excitons can be dissociated to electrons and holes to yield a photocurrent in the external circuit. We then aim to extend the spectral window of the solar cells to higher wavelength region by increasing the diameter of PbS nanoparticles to make the cells further NIR-active. We observe that the short-circuit current (JSC) shows a peak when the diameter of PbS nanoparticles increases. Here, the spectral window can be extended till conduction band-edge of PbS quantum dots falls below that of TiO2 nanostructures cutting off the electron-transfer pathway. The NIR-active photovoltaic solar cells yield a short-circuit current (JSC) of 1.0 mA/cm2, open-circuit voltage (VOC) of 0.42 V, and power conversion efficiency (η) of 0.16% and remain operative till 1200 nm.

Transient Electro-Graphitization of MOFs Affecting the Crystallization of Ruthenium Nanoclusters for Highly Efficient Hydrogen Evolution - Karim, Golam Masud; Patra, Amalika; Deb, Sujit Kumar; Upadhya, Hemanta; Das, Snehasish; Mukherjee, Priyam; Ahmad, Waleed; Barman, Narad; Thapa, Ranjit; Dambhare, V, Neha; Rath, Arup Kumar; Das, Jaysri; et al. (ADVANCED FUNCTIONAL MATERIALS, 2024)
Keywords: amorphous ruthenium; crystallization control; graphitic nanostructure